Decorative motifs and depictions of Gods with their consorts - Temples of India Project Team (Jio Institute, 2024)
The ceiling of the mukhamandapa (front porch) is square in shape and intricately carved with floral motifs and figures of gods accompanied by their consorts. The corners of the ceiling are decorated with half-lotus medallions. The inner square repeats the same pattern and the innermost square depicts lobbed arched four-petal flowers at the centre and on each side. Notably, the corners of the innermost square feature depictions of Ganesha, Brahma, Vishnu, and another deity with their consorts, flanked by female attendants.